Cutaneous polyautoimmunity in two unrelated dogs: pemphigus foliaceus and generalized discoid lupus erythematosus. Issue 4 (27th April 2020) - Levy, Britt J.; Linder, Keith E.; Mamo, Lisa B.; Herrmann, Ina; Bizikova, Petra
Abstract : Background: Polyautoimmunity, the concurrent expression of two or more distinct autoimmune diseases (ADs) in a single individual, is a known phenomenon in humans and has been rarely reported in dogs. To the best of the authors' knowledge, comorbid pemphigus foliaceus (PF) and generalized discoid lupus erythematosus (GDLE) has not been reported in dogs. Hypothesis/Objectives: To describe the clinical, histological and immunological features and treatment outcome of two unrelated dogs with comorbid PF and GDLE. Animals: One 10‐year‐old, spayed German shepherd dog and one 8‐year‐old, castrated American Staffordshire terrier presented for evaluation of a symmetrical, facial‐ and/or pedal‐dominant pustular dermatitis with concurrent, truncal scaly plaques. Methods: For each dog, clinicopathological characterization included physical examination, lesion cytological evaluation, bacterial culture and sensitivity testing, skin histopathological investigation and direct and indirect immunofluorescence testing. Additional diagnostic imaging and haematological testing was performed to exclude extracutaneous disease. Results: Both dogs exhibited lesions clinically and histologically compatible with PF and GDLE. Moreover, one dog exhibited generalized leucotrichia and chronic superficial keratitis. Remission was achieved with immunosuppressive dosages of prednisolone [high‐dose pulse (Case 1) or standard immunosuppressive dosage (Case 2)] and ciclosporin (5–6 mg/kg/day). Tissue‐bound antikeratinocyte immunoglobulin (Ig)G and IgM were detected in both dogs. A weak basement membrane zone deposit of C3 was seen in one dog. Circulating antikeratinocyte and anti‐desmocollin‐1 IgG were detected in one dog. Conclusions and clinical importance: Cutaneous polyautoimmunity can occur in the dog. Depending on the specific disease combinations, overlapping clinical features may present diagnostic and/or therapeutic challenges. Moreover, these cases should be monitored for development of additional cutaneous or extra‐cutaneous AD(s). Abstract : Background – Polyautoimmunity, the concurrent expression of two or more distinct autoimmune diseases (ADs) in a single individual, is a known phenomenon in humans; it is rarely reported in dogs. To the best of the authors' knowledge, comorbid pemphigus foliaceus (PF) and generalized discoid lupus erythematosus (GDLE) has not been reported in dogs. Hypothesis/Objectives – To describe the clinical, histological and immunological features and treatment outcome of two unrelated dogs with comorbid PF and GDLE. Conclusions and clinical importance – Cutaneous polyautoimmunity can occur in the dog. Depending on the specific disease combinations, overlapping clinical features may present diagnostic and/or therapeutic challenges. Moreover, these cases should be monitored for development of additional cutaneous or extra‐cutaneous AD(s). Résumé: Contexte: La poly‐auto‐immunité, l'expression concomitante de deux ou plus de maladies auto‐immunes (ADs) chez un même individu est un phénomène connu chez l'homme ; c'est rarement décrit chez le chien. A la connaissance des auteurs, l'association d'un pemphigus foliacé (PF) et d'un lupus érythémateux discoïde (GDLE) n'a pas été décrit chez le chien. Hypothèses/Objectifs: Décrire les données clinques, histologiques et immunologiques ainsi que l'évolution de deux chiens non liés atteints de PF et GDLE. Sujets: Une chienne berger allemand stérilisée de 10 ans et un american staffordshire terrier castré de 8 ans présentés en consultation pour une dermatite pustuleuse à dominante faciale/podale symétrique associée à des plaques squameuses tronculaires. Méthodes: Pour chaque chien, un examen physique incluait une caractérisation clinicopathologique, une évaluation cytologique, une culture bactériologique et des tests de sensibilité, un examen histopathologique et des tests d'immunofluorescence directes et indirectes. Des test d'imagerie et hématologiques supplémentaires ont été réalisés pour exclure des maladies extra‐cutanées. Résultats: Les deux chiens ont montré des lésions cliniques et histologiques compatibles avec PF et GDLE. En outre, un chien a montré une leucotrichie généralisée et une kératite superficielle chronique. Une rémission a été obtenue avec des doses immunosuppressives de prednisolone [doses élevées pulsées (Cas 1) ou dose immunosuppressive standard (Cas 2)] et ciclosporine (5–6 mg/kg/jour). Des immunoglobulines (Ig)M et IgG antikératinocytes ont été détectées chez les deux chiens. Un dépot faible de C3 au niveau de la membrane basale a été observé chez un chien. Les antikératinocytes circulants et IgG anti‐desmocolline 1 ont été détectés chez un chien. Conclusions et importance clinique: La poly‐auto‐immunité cutanée peut se produite chez le chien. En fonction des combinaisons spécifiques des maladies, un recoupement des lésions cliniques peut représenter un défit diagnostic et/ou thérapeutique. En outre, ces cas devraient être suivis pour le développement d'autres atteintes cutanées ou extracutanées. Resumen: Introducción: la poliautoinmunidad, la expresión conjunta de dos o más enfermedades autoinmunes (ADs) distintas en un solo individuo, es un fenómeno conocido en humanos; rara vez se ha reportado en perros. A entender de los autores, pénfigo foliáceo (PF) y lupus eritematoso discoide generalizado (GDLE) no se han reportado en perros en aparición conjunta. Hipótesis/Objetivos: describir las características clínicas, histológicas e inmunológicas y el resultado del tratamiento de dos perros no relacionados con PF y GDLE de aparición conjunta. Animales: un perro pastor alemán castrado de 10 años de edad y un American Staffordshire terrier castrado de 8 años de edad presentados para evaluación de una dermatitis predominantemente pustular simétrica, facial y/o podal y placas escamosas truncales concomitantes. Métodos: en cada perro, la caracterización clínico‐patológica incluyó examen físico, evaluación citológica de la lesión, cultivo bacteriano y pruebas de sensibilidad, investigación histopatológica de la piel y pruebas de inmunofluorescencia directa e indirecta. Se realizó un diagnóstico por imagen adicional y una investigación hematológica para excluir enfermedades extracutáneas. Resultados: Ambos perros exhibieron lesiones clínicamente e histológicamente compatibles con PF y GDLE. Además, un perro presentó leucotrichia generalizada y queratitis superficial crónica. La remisión se logró con dosis inmunosupresoras de prednisolona [pulso de dosis alta (caso 1) o dosis inmunosupresora estándar (caso 2)] y ciclosporina (5–6 mg/kg /día). Se detectaron inmunoglobulinas (Ig) G e IgM antiqueratinocitos unidas a tejidos en ambos perros. Se observó un depósito débil de C3 en la membrana basal epidermal en un perro. Se detectaron IgG antiqueratinocitos y anti‐desmocollin‐1 circulantes en un perro. Conclusiones e importancia clínica: la poliautoinmunidad cutánea puede ocurrir en el perro. Dependiendo de las combinaciones de enfermedades específicas, las características clínicas superpuestas pueden presentar dificultades diagnósticas y/o terapéuticas. Además, estos casos deben ser controlados por el posible desarrollo de AD(s) cutáneas o extracutáneas adicionales. Zusammenfassung: Hintergrund: Die Polyautoimmunität, der momentane Ausdruck für zwei oder mehr unterschiedliche Autoimmunerkrankungen (ADs) in einem einzigen Individuum ist ein bekanntes Phänomen beim Menschen; es wird bei Hunden nur selten beschrieben. Nach bestem Wissen der Autoren, wurde bisher eine Komorbidität von Pemphigus foliaceus (PF) und generalisiertem discoiden Lupus Erythematosus (GDLE) bei Hunden nicht beschrieben. Hypothese/Ziele: Die Beschreibung der klinischen, histologischen und immunologischen Merkmale und Behandlungserfolge zweier nicht verwandter Hunde mit Komorbidität von PF und GDLE. Tiere: Eine 10 Jahre alte kastrierte Deutsche Schäferhündin und ein 8 Jahre alter kastrierter American Staffordshire Terrier wurden zur Evaluierung einer symmetrischen, Gesichts und/oder die Füsse‐dominierender pustulöser Dermatitis mit gleichzeitigen schuppigen Plaques am Rumpf vorgestellt. Methoden: Für jeden Hund beinhaltete die klinisch‐pathologische Charakterisierung eine physische Untersuchung, eine zytologische Evaluierung der Läsionen, eine Bakterienkultur und Antibiogramm, eine histopathologische Untersuchung der Haut und direkte und indirekte Immunfluoreszenz. Zusätzliche Bildgebende Diagnostik und hämatologische Untersuchungen wurden durchgeführt, um Erkrankungen, die nicht mit der Haut im Zusammenhang standen, auszuschließen. Ergebnisse: Beide Hunde zeigten Hautveränderungen, die klinisch und histologisch mit PF und GDLE vergleichbar waren. Zusätzlich zeigte ein Hund eine generalisierte Leukotrichie und eine chronische superfizielle Keratitis. Eine Remission wurde mit immunsuppressiven Dosen von Prednisolon [hochdosierte Pulstherapie (Fall 1) oder eine Standard immunsuppressive Dosis (Fall 2)] und Ciclosporin (5‐6 mg/kg/Tag) erzielt. An Gewebe gebundene Antikeratinozyten Immunglobulin (Ig) G und IgM wurden bei beiden Hunden gefunden. Eine schwache Ablagerung in der Basalmembran von C3 wurde bei einem Hund gefunden. Bei einem Hund wurden zirkulierende Antikeratinozyten und Anti‐Desmocollin‐1 IgG festgestellt. Schlussfolgerungen und klinische Bedeutung: Eine kutane Polyautoimmunität kann beim Hund auftreten. Abhängig von den spezifischen Krankheitskombinationen, könnten überlappende klinische Merkmale diagnostische und/oder therapeutische Herausforderungen darstellen. Darüber hinaus sollten diese Erkrankungen auf die Entwicklung zusätzlicher kutaner oder extra‐kutaner AD(s) untersucht werden. 要約: 背景: 単一個体における2つ以上の異なる自己免疫疾患（AD）を同時発現する多発性自己免疫性疾患は、人医療においては既知の現象である。犬ではほとんど報告されていない。著者の知る限り、落葉性天疱瘡（PF）および全身性円板状エリテマトーデス（GDLE）を併発した犬は報告されていない。 仮説/目的: 本研究の目的は、PFとGDLEが併発した血縁のない2頭の犬の臨床的、組織学的、免疫学的特徴と治療成績を説明することであった。 供試動物: 1頭の10歳避妊雌ジャーマン・シェパード・ドッグおよび1頭の8歳去勢雄アメリカン・スタッフォードシャー・テリアが、左右対称性の顔面および/または肢を主要病変とする膿疱性皮膚炎と同時発生した体幹の鱗状局面の評価のため来院した。 方法: 各犬の臨床病理学的特性の評価には、身体検査、病変細胞学的評価、細菌培養および薬剤感受性検査、皮膚組織病理学的検査、直接および間接免疫蛍光検査を含んだ。皮膚以外の疾患を除外するため、追加画像診断および血液学的調査を実施した。 結果: どちらの犬においても、PFおよびGDLEと臨床的および組織学的に適合した病変を示した。さらに、1頭の犬は、全身性白毛症および慢性表在性角膜炎を呈した。免疫抑制量のプレドニゾロン[高用量パルス（症例1）または標準免疫抑制量（症例2）]およびシクロス​​ポリン（5‐6 mg / kg /日）によって寛解に至った。組織結合抗ケラチノサイト免疫グロブリン（Ig）GおよびIgMがどちらの犬でも検出された。 C3の基底膜領域における弱い沈着が1頭の犬に認められた。循環抗角化細胞および抗デスモコリン‐1 IgGが1頭の犬で検出された。 結論と臨床的重要性: 犬では皮膚自己免疫疾患が起こる。特定の疾患の組み合わせに応じて、重複する臨床的特徴は診断および/または治療上の課題が認められる場合がある。さらに、本症例は皮膚または皮膚以外のADの追加の発生を監視する必要がある。 摘要: 背景: 多发性自身免疫是已知的人类疾病，一个病患同时表现两种或两种以上不同的自体免疫病 (ADs)；在犬鲜有报道。据作者所知，尚未有过关于犬并发落叶型天疱疮 (PF) 和全身性盘状红斑狼疮 (GDLE) 的报告 。 假设/目的: 描述两只无血缘关系、并发PF和GDLE的犬，报告其临床、组织学和免疫学特征以及治疗效果。 动物: 一只10岁切除卵巢的德国牧羊犬和一只8岁去势的美国斯塔福德郡㹴犬，评估其对称性面部和/或爪部脓疱性皮炎，以及并发的躯干鳞屑性斑块。 方法: 对于每只犬，临床病理学表征包括体格检查、病变细胞学评估、细菌培养和药敏试验、皮肤组织病理学研究以及直接和间接免疫荧光试验。另外进行影像学诊断和血液学检查，以排除皮肤系统外疾病。 结果: 两只犬均表现出与PF和GDLE临床和组织学相符的病变。此外，一只犬表现出全身性白毛病和慢性浅表性角膜炎。使用免疫抑制剂量的泼尼松龙 [高剂量脉冲（病例 1），或标准免疫抑制剂量（病例 2）] 和环孢素（5‐6 mg/kg/天）达到缓解。在两只犬身上均检测到组织结合的抗角质细胞免疫球蛋白 (Ig) G 和 IgM。在一只犬身上观察到C3的弱基底膜带沉积。在一只犬身上检测到循环抗角质细胞和抗桥粒糖蛋白‐1 IgG。 结论和临床重要性: 皮肤多发性自体免疫可发生在犬身上。根据特定的疾病组合、重叠的临床特征可能带来诊断和/或治疗挑战。此外，应监测这些病例是否发生其他皮肤或皮肤系统外ADs。 Resumo: Contexto: A poliautoimunidade, expressão simultânea de duas ou mais doenças autoimunes (DAs) distintas em um único indivíduo, é um fenômeno conhecido em humanos; este raramente é relatado em cães. De acordo com o conhecimento dos autores, ainda não há relatos em cães de pênfigo foliáceo (PF) e o lúpus eritematoso discóide generalizado (GDLE) em comorbidade. Hipótese/Objetivos: Descrever as características clínicas, histológicas e imunológicas e o resultado do tratamento de dois cães não relacionados com PF e GDLE em comorbidade. Animais: Um cão pastor alemão de 10 anos, castrado e um American Staffordshire terrier castrado de 8 anos de idade foram apresentados para avaliação de uma dermatite pustular simétrica, predominantemente facial e/ou a podal com placas descamativas concomitantes no dorso. Métodos: Para cada cão, a caracterização clínico‐patológica incluiu exame físico, avaliação citológica lesional, cultura bacteriana e teste de sensibilidade, investigação histopatológica da pele e teste direto e indireto de imunofluorescência. Diagnóstico por imagem adicional e investigação hematológica foram realizadas para excluir doença extracutânea. Resultados: Ambos os cães apresentaram lesões clinica e histologicamente compatíveis com PF e GDLE. Além disso, um cão exibiu leucotriquia generalizada e ceratite superficial crônica. A remissão foi alcançada com dosagens imunossupressoras de prednisolona [pulso de alta dose (Caso 1) ou dosagem imunossupressora padrão (Caso 2)] e ciclosporina (5–6 mg / kg / dia). Detectou‐se a presença de imunoglobulina (Ig) anti‐queratinócito G e a IgM ligadas ao tecido em ambos os cães. Um depósito fraco de C3 na zona da membrana basal foi observado em um cão. Anticorpos IgG anti‐queratinócitos e anti‐desmocolina‐1 circulantes foram detectados em um cão. Conclusões e importância clínica: A poliautoimunidade cutânea pode ocorrer no cão. Dependendo das combinações específicas de doenças, as características clínicas sobrepostas podem apresentar desafios diagnósticos e/ou terapêuticos. Além disso, esses casos devem ser monitorados quanto ao desenvolvimento de Das cutâneas ou extra‐cutâneas adicionais.